Kesenian Topeng Barongan dalam Ritual Murwakala di Kabupaten Blora - Fivin Bagus Septiya Pambudi (SULUH: Jurnal Seni Desain Budaya, 2018)
Murwakala ritual is a Ruwatan ritual, namely ngruwat Wong Sukerta, because the Blora people believe in the existence of Wong Sukerta. The trust of Blora residents who consider Barongan has magical powers that are believed to be able to drive away the evil spirits and reject these reinforcements to make barongan a means of ceremonies in the Murwakala ritual.Barongan mask art in Murwakala includes Traditional Murwakala rituals and Murwakala rituals on stage performances. Barongan is a form of communal art of the community, whose presence is closely related to community traditions, such as the use of Barongan as a means of Murwakala ritual. The murwakala ritual tradition was originally carried out traditionally and later developed into Murwakala stage performances. The murwakala ritual is based on the belief of the Blora community about the existence of wong sukerta (the person whose birth in colonialism brings bad luck) which must be complicated by holding a Murwakala ritual using the Barongan mask. The function of the Barongan blora mask in the murwakala ritual, namely Barongan murni, as a means of Murwakala and Barongan rituals as a means of ritual Murwakala stage performances.